Conservation and Identity Selection of Cationic Residues Flanking the Hydrophobic Regions in Intermediate Filament Superfamily - Zhang, Wenbo; Liu, Mingwei; Dupont, Robert L.; Huang, Kai; Yu, Lanlan; Liu, Shuli; Wang, Xiaoguang; Wang, Chenxuan (Frontiers in Chemistry, 2021)
The interplay between the hydrophobic interactions generated by the nonpolar region and the proximal functional groups within nanometers of the nonpolar region offers a promising strategy to manipulate the intermolecular hydrophobic attractions in an artificial molecule system, but the outcomes of such modulations in the building of a native protein architecture remain unclear. Here we focus on the intermediate filament (IF) coiled-coil superfamily to assess the conservation of positively charged residue identity via a biostatistical approach. By screening the disease-correlated mutations throughout the IF superfamily, 10 distinct hotspots where a cation-to-cation substitution is associated with a pathogenic syndrome have been identified. The analysis of the local chemical context surrounding the hotspots revealed that the cationic diversity depends on their separation distance to the hydrophobic domain. The nearby cationic residues flanking the hydrophobic domain of a helix (separation < 1 nm) are relatively conserved in evolution. In contrast, the cationic residues that are not adjacent to the hydrophobic domain (separation > 1 nm) tolerate higher levels of variation and replaceability. We attribute this bias in the conservation degree of the cationic residue identity to reflect the interplay between the proximal cations and the hydrophobic interactions.